2019
DOI: 10.1088/1361-6587/aafbbf
|View full text |Cite
|
Sign up to set email alerts
|

Current sheets in planetary magnetospheres

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
(146 reference statements)
0
14
0
Order By: Relevance
“…In [68,69], the characteristic shape of exoplanetary magnetosphere streamlined by star wind flow are considered with magnetopause, magnetosheath, and magnetotail. In such conditions, we expect similar processes of magnetospheric perturbation as magnetic storms and substorms (e.g., [6]). Like the Earth, the processes of atmospheric escape from exoplanets should be considered, taking into account the form of planetary magnetic fields.…”
Section: The Structure Of Astrosphere As the Possible Indication To Tmentioning
confidence: 85%
See 1 more Smart Citation
“…In [68,69], the characteristic shape of exoplanetary magnetosphere streamlined by star wind flow are considered with magnetopause, magnetosheath, and magnetotail. In such conditions, we expect similar processes of magnetospheric perturbation as magnetic storms and substorms (e.g., [6]). Like the Earth, the processes of atmospheric escape from exoplanets should be considered, taking into account the form of planetary magnetic fields.…”
Section: The Structure Of Astrosphere As the Possible Indication To Tmentioning
confidence: 85%
“…The process of accumulation is far from being straightforward because of the novelty of the topic. In particular, it seems very attractive to suppose that the exoplanets have magnetic fields that are to some extent similar to the geomagnetic field as well as the stars in the planetary system with particular exoplanets having a magnetic field that is to some extent similar to the solar magnetic field [5,6]. In regards to first attempts to observe the magnetic fields of exoplanets see, e.g., [7].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetized electrons prevent the growth of current sheet instabilities and support very crucial TCS metastable properties. Due to electron effects, TCS may remain stable for a long time, holding the accumulated magnetic energy, but at some moments, spontaneous reconnection results in destruction of equilibrium structure and explosive energy release (Zelenyi et al, 2011(Zelenyi et al, , 2016(Zelenyi et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that, in this hybrid regime the equations describing the motion of magnetized electrons are scale free, and cannot provide an estimation of the thickness of electron current layer. Numerical solution of these equations used in the earlier studies (e.g., Malova et al, 2012Malova et al, , 2013Malova et al, , 2017Zelenyi et al, 2004Zelenyi et al, , 2011Zelenyi et al, , 2019 have shown the presence of a strong electron current in the center of the TCS, but because of the numerical limitations these calculations have given only rough estimates of the thickness and amplitude of electron current peak. Zelenyi et al (2020) have proposed a novel analytical model of the multiscale TCS that provides a universal expression describing the embedded electron STCS in dependence of the TCS characteristics.…”
mentioning
confidence: 99%